Primary fallopian tube carcinoma: the Queensland experience. Issue 1 (1st January 2001) - Obermair, A.; Taylor, K. H.; Janda, M.; Nicklin, J. L.; Crandon, A. J.; Perrin, L.
Abstract : The pupose of this study was to review the experience with fallopian tube carcinoma in Queensland and to compare it with previously published data. Thirty-six patients with primary fallopian tube carcinoma treated at the Queensland Gynaecological Cancer Center from 1988 to 1999 were reviewed in a retrospective clinicopathologic study. All patients had primary surgery and 31/36 received chemotherapy postoperatively. Abnormal vaginal bleeding (15/36) and abdominal pain (14/36) were the most common presenting symptoms at the time of diagnosis. Median follow-up was 70.3 months and the median overall survival was 68.1 months. Surgical stage I disease ( P = 0.02) and the absence of residual tumor after operation ( P = 0.03) were the only factors associated with improved survival. Twenty of the 36 patients (55%) presented with stage I disease and survival was 62.7% at 5 years. No patient with postoperative residual tumor survived. The majority of the patients with fallopian tube carcinoma present with stage I disease at diagnosis, but their survival probability is low compared with that of other early stage gynecological malignancies. If primary surgical debulking cannot achieve macroscopic tumor clearence, the chance of survival is extremely low.